GLOBAL TRENDS OF MODERN INCLUSIVE ECONOMY - Iryna Zvarych; Oksana Brodovska (Agora International Journal of Economical Sciences (AIJES), 2023)
The purpose of the article is to highlight and work out the global trends of the modern inclusive economy. Methodologically outline the main concepts on which modern inclusive economies are based, taking into account the war in Ukraine, climate challenges, displacement of migration centers. The key point is the development of a model of a successful modern and exclusive economy. Research on building inclusive workplaces, inclusion and entrepreneurship, corporate responses to the refugee and forced migration crisis, delivery of essential services to disadvantaged groups, enriched by diverse practitioners' perspectives. Although the global economy began to rebound in 2021, bringing some improvement in unemployment, recovery remains elusive and fragile. By the end of 2021, global economic recovery had been hampered by new waves of COVID-19 infections, rising inflationary pressures, major supply-chain disruptions, policy uncertainties and persistent labour market challenges. ompanies need to ensure that they implement the right sustainable technologies in all of their processes and in every area of their operations in providing the inclusive economy, increasing implementation of the idea of circular economy. In deciding which circular economy actions to prioritise and integrate into climate-focused policies and measures, countries and companies are to be able to compare the relative merits, as well as emissions reductions, of individual circular economy measures.
Keywords: 330